Quality of life and sleep in diabetes mellitus patients - Demir, Mustafa (My University, 2019)
Aim: As in other chronic diseases, symptom and signs of psychiatric disorders are more common in patients with diabetes mellitus(DM) than in the general population. The aim of this study was to evaluate the quality of life and sleep in DM patients.Material and Methods: A total of 100 DM patients, 56 (56%) female and 44 (44%) male, were included in the study. Control groupconsisted of 100 healthy volunteers (53 females (53%) and 47 males (47%)). The sociodemographic and clinical characteristics ofparticipants were recorded. Patients were asked to complete the 36-Item Short-Form Health Survey (SF–36) and Pittsburgh SleepQuality Questionnaire (PSQ). Score calculations were made according to the survey results. Data were analyzed using SPSS 14program.Results: A statistically significant difference was found between the patient and control group in all sub-parameters ofquality of life (p <0.05). When the mean of all sub-parameters was evaluated, it was detected that all quality of life scoresof the patients were lower than the control group. PSQ subscale scores were significantly different between patient andcontrol groups (p <0.001). The total PSQ score of the patients was 9.14 ± 4.07 and the control group was 5.38 ± 3.30.Conclusion: According to our study results, impaired quality of life and sleep observed in DM patients. We think that the evaluationof sociodemographic variables that may affect the quality of life and sleep quality and accordingly planning the treatment strategywould have positive contributions in the treatment of DM.
Keywords: Genel ve Dahili Tıp